1996
DOI: 10.1074/jbc.271.1.425
|View full text |Cite
|
Sign up to set email alerts
|

Cataractogenesis in Transgenic Mice Containing the HIV-1 Protease Linked to the Lens αA-Crystallin Promoter

Abstract: Several lines of transgenic mice were generated with either active or inactive forms of the human immunodeficiency virus type 1 (HIV-1) protease gene under the control of the mouse lens alpha A-crystallin promoter. Mice bearing the inactive protease coding sequence displayed no gross abnormalities in the lens, while mice with the active protease developed time-dependent bilateral cataracts. One line, TG61, developed cataracts in utero while the second line, TG72, developed cataracts postnatally. TG61 mice, hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…Our observations of APH and cataract development are similar to those described in the previously reported studies of transgenic mice expressing HIV-1 protease in the lens under the control of ␣A-crystallin promoter (40). Mice with active HIV-1 protease developed cataract, and mice bearing inactive protease had normal lens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observations of APH and cataract development are similar to those described in the previously reported studies of transgenic mice expressing HIV-1 protease in the lens under the control of ␣A-crystallin promoter (40). Mice with active HIV-1 protease developed cataract, and mice bearing inactive protease had normal lens.…”
Section: Discussionsupporting
confidence: 90%
“…Proteolysis of crystallins is known to occur in nonhuman lenses during aging (29 -32) and in animal models of cataract (33)(34)(35)(36). Extensive studies of calpain, including Lp82 (37)(38)(39), and of transgenic mice expressing the HIV protease (40) have confirmed that proteolysis of crystallins is one of the factors in cataract formation. However, unlike in rodent cataract, lensspecific calpain Lp82 has not been found to be involved in human cataractogenesis and, because HIV protease is foreign to the lens, other proteases are responsible for the proteolysis in human agerelated cataract lenses and diabetic lenses.…”
mentioning
confidence: 99%
“…3). The 25-kDa and 23-kDa bands only displayed reactivity to the N-terminal directed anti-MIP- (1)(2)(3)(4)(5)(6)(7)(8). Degradation of the MIP26 in organ culture was from the C terminus and mimicked the degradation in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Cataract formation is dependent on the HIV-1 protease, because transgenic mice expressing an inactive HIV-1 protease in the lens remain cataract-free as do TG 72 mice that are administered HIV-1 protease inhibitors (6). In homozygous TG 72 mice, lenses show refractive index changes prior to cataract formation.…”
mentioning
confidence: 99%
“…More recently, cataracts have been described in mice transgenic for the HIV-1 protease under the control of the lens alpha A-crystallin promoter. 15,16 The authors concluded that proteolysis of lens proteins, presumably induced by the viral protease, was responsible for cataract formation. Most recently, Dickie 17 reported on cataracts occurring in five transgenic lines of mice derived from four constructs: intact HIV-1 proviral DNA under the control of the HIV-1 long terminal repeat (LTR) or a chimeric HIV-1/MMTV LTR, a gag-pol deleted genome and the Nef gene.…”
Section: Introductionmentioning
confidence: 99%